Komunikasi Antar Umat Beragama di Kota Palopo (Perspektif Kajian Dakwah) - Masmuddin, Masmuddin (IAIN Palangka Raya, 2017)
Islam is a dakwah religion, that obliges all adherents to convey the messages of the teachings contained in it as a life guidance. Therefore, all Muslims should convey the teachings of Islam to all mankind in a good way according to the instructions of the Qur'an and the Prophet Muhammad